2019
DOI: 10.1136/bcr-2019-231129
|View full text |Cite
|
Sign up to set email alerts
|

Novel missense mutation in the ATP1A2 gene associated with atypical sporadic hemiplegic migraine

Abstract: Hemiplegic migraine (HM) is a rare subtype of migraine with aura in which attacks include transient motor weakness or hemiparesis that can last several days. HM is linked to mutations in three different genes, CACNA1A, ATP1A2 and SCN1A, which encode for ion transporters. The clinical spectrum includes atypical symptoms such as impaired consciousness, epileptic seizures, permanent cerebellar ataxia or mental retardation. We describe a novel mutation found in the ATP1A2 gene in a patient with late-onset HM. His … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Table 1 includes clinical presentations, imaging findings, and genetic testing if performed for patients with hemiplegic migraines with an ATP1A2 mutation undergoing severe attacks published in the last ten years [6,9,10,15,[17][18][19][20][21][22][23][24]. Perfusion studies on FHM2 patients have demonstrated both hypo-and hyperperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 includes clinical presentations, imaging findings, and genetic testing if performed for patients with hemiplegic migraines with an ATP1A2 mutation undergoing severe attacks published in the last ten years [6,9,10,15,[17][18][19][20][21][22][23][24]. Perfusion studies on FHM2 patients have demonstrated both hypo-and hyperperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cerebellar involvement with a gaze-evoked nystagmus and progressive ataxia has been associated with in FHM type 1 (FHM1) in about 60% of cases, but is rare in FHM type 2 (FHM2). 1 8 18 19 Moreover, some mutations of CACNA1A or ATP1A2 have been associated with mental retardation and cognitive impairment after severe and recurrent episodes [20][21][22][23] ; early onset attacks, coma and seizure are considered the main risk factors for this kind of complication. 1 24 More recently, 50% of children (aged 3-18 years) with a pathogenic CACNA1A mutation associated with HM and other benign paroxysmal events (torticollis, vertigo or tonic upgaze) showed an heterogeneous cognitive dysfunction without a specific cognitive profile, mainly associated with vermian cerebellar atrophy for these early onset CACNA1A-associated phenotype was proposed a classification as 'neurodevelopmental disorders', suggesting thus a close follow-up of psychomotor development and academic performances.…”
Section: Chronic Symptomsmentioning
confidence: 99%
“…We previously described the case of a patient with late-onset SHM (missense mutation of the ATP1A2 gene) with hypertension and severe carotid stenoses. 21 Conversely, recurrent TIAs can be evocative of SHM in patients with rare syndromes who fulfil criteria for HM. 61 Nevertheless, TIAs and strokes have a sudden onset, while HM typically shows gradual progressive spread with aura 1 ; the neuroimaging can be helpful to distinguish among these conditions, but the timing of the headache also provides relevant information, because the headache usually follows the motor weakness in HM and precedes the weakness in haemorrhagic strokes.…”
Section: Introductionmentioning
confidence: 99%
“…The duration of symptoms is usually 20–60 min. In some cases, the aura and hemiplegia may onset quickly and simulate an ischaemic attack [ 17 ]. Complete recovery from attacks is the rule, but in severe HM, hemiplegia and altered consciousness may persist for weeks until normal [ 3 ].…”
Section: Resultsmentioning
confidence: 99%